The Implementation of Islamic Local Content in Building Character Education at Junior High Shcool Al Amanah Bandung - Mohamad Erihadiana (Jurnal Pendidikan Islam, 2018)
Education system constitutes an important stage in growing, developing, and strengthening the character of younger generation. This means that the objectives of education at the institutional level (school) can be a representation of the goals of national education that covers character education. The study aimed to describe the implementation of the curriculum of local Islamic content through curricular, co-curricular and extracurricular programs at SMP (Sekolah Menengah Pertama/junior high school) Al-Amanah Cileunyi to shape the character of students in accordance with Islamic morals. This study applied a naturalistic qualitative approach. The approach is used due to the problems that are currently occurring naturally at the present time, namely student character education at SMP Al-Amanah Cileunyi. The research finding showed that  SMP Al-Amanah Cileunyi has a local Islamic content curriculum, both as a subject matter and an extra-curricular activity, Islamic local content that applies at SMP Al-Amanah Cileunyi featuring character values that are originated from the Islamic teachings, and eighteen national character values as determined by the government, and the implementation of Islamic local content is through the activities of self-development, habituation, extra-curricular, exemplary, and the integration of character education within learning process. However, there are some problems encountered in its implementation, among others due to inconsistent attitudes of school community and the gap between character education programs and their implementation. The result of character education through the implementation of Islamic local content is shown by the qualitative scores in the report book, and the increasing trust of parents and the community to SMP Al-Amanah Cileunyi.